CTNI-68. FIREFLY-1 (PNOC026): PHASE 2 STUDY OF PAN-RAF INHIBITOR TOVORAFENIB IN PEDIATRIC AND YOUNG ADULT PATIENTS WITH RAF-ALTERED RECURRENT OR PROGRESSIVE LOW-GRADE GLIOMA OR ADVANCED SOLID TUMORS. (14th November 2022) - Kilburn, Lindsay; Landi, Daniel; Leary, Sarah; Ziegler, David; Baxter, Patricia; Franson, Andrea; McCowage, Geoffrey; Waanders, Angela; Van der Lugt, Jasper; Oren, Michal Yalon; Gerber, Nicolas; Gottardo, Nicholas; et al.
Abstract: BACKGROUND: RAF alterations are oncogenic drivers found in most pediatric low-grade gliomas (LGGs). Tovorafenib is an investigational, oral, selective, CNS-penetrant, small molecule, type II pan‑RAF inhibitor. METHODS: FIREFLY-1 (NCT04775485) is a multicenter phase 2 study evaluating the safety and efficacy of tovorafenib monotherapy. Registrational arm 1 enrolled patients with recurrent/progressive LGG harboring an activating BRAF alteration. Patients aged 6 months–25 years who progressed following ≥ 1 prior line of systemic therapy were eligible. Tovorafenib 420 mg/m2 (≤ 600 mg) was administered weekly (tablet or liquid suspension formulation) until progression or for ≥ 26, 28-day cycles. The primary endpoint (arm 1) was overall response rate, as defined by RANO criteria, per independent review. RESULTS: As of April 14, 2022, 25 patients were enrolled to arm 1 and had ≥ 6 months of follow-up. Median age at enrollment was 8 years (range 3–18). Most patients had astrocytomas (92%), 48% with optic pathway involvement. Patients were heavily pretreated (56% with ≥ 3 prior lines of therapy), and 72% previously received MAPK pathway-targeted agents. Tumors harbored BRAF fusions (84%) or BRAF V600E mutations (16%). Per independent assessment, partial responses (1 unconfirmed) were seen in 14 (64%) of 22 evaluable patients, with 6 additional patients having stable disease, and a clinical benefit rate of 91%. Responses were achieved in tumors with BRAF fusions and V600E mutations. Most treatment-emergent adverse events (AEs) were grade 1 or 2 (96%). The most common grade ≥ 3 AEs were anemia (12%), vomiting, increased blood creatinine phosphokinase and maculopapular rash (8% each). Seven patients (28%) required dose modification for treatment-related AEs; no patients discontinued tovorafenib due to AEs. Updated results, including efficacy per RAPNO assessments will be presented. CONCLUSIONS: Tovorafenib was generally well tolerated and showed encouraging evidence of antitumor activity in children with pretreated BRAF -altered LGG.